KOMUNIKASI INTERNAL GRAND JATRA HOTEL PEKANBARU DALAM MENGIMPLEMENTASIKAN PROGRAM EMPLOYEE BRANDING - Veronika Sri Lestari Yudiandani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The employee branding program is a forum formed by Grand Jatra Hotel Pekanbaru to create increasingly qualified employees in their profession. This program is formed by considering the relationship between the company and employees. The form of the employee branding program at Grand Jatra is training, evaluation, competition and awards. The awards applied by Grand Jatra Hotel are various types, namely best therapist, best room, best smile, best wine, best grooming, best ambassador, and the highlight is best employee of the year. The purpose of establishing an employee branding program is to make employees more comfortable working in Grand Jatra, so that employees can develop their talents, foster a healthy spirit of competition and employees are increasingly proactive in their work. The purpose of this study was to determine the form of the employee branding program and the form of Grand Jatra Hotel Pekanbaru's internal communication in implementing the employee branding program. This study uses a qualitative descriptive research method. Data collection techniques used are interviews, observation and documentation. The subjects involved in this study were determined based on a purposive technique, which consisted of HR Manager, HRD, SPA Manager, FO Manager, Senior Room Boy, Embassy Coordinator, GSA, and Senior Laundry. Data analysis techniques used are using the interactive data analysis model of Miles and Huberman, using the technique of checking the validity of the data, namely triangulation and extension of participation.       The results showed that the form of an employee branding program consisted of training, evaluation, competition and finally the award. The form of Grand Jatra Hotel Pekanbaru's internal communication the organization participates in paying attention to the people who work in the organization by creating a safe and comfortable communication and organizational climate for the company. Internal communication used is in the form of vertical, from top to bottom, from the bottom up, which is semi-informal depending on the conditions in the delivery of information and horizontally which is interpreted by communication between employees who tend to be informal, and information is easier to obtain. Keywords:  Internal communication, Employee branding, Implementation